STRATEGI PEMBELAJARAN DENGAN BRAINBASED LEARNING UNTUK MENCAPAI HASIL BELAJAR YANG OPTIMAL - Novrianti Novrianti (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This study aims to determine the effect of interactions between the Contextual Brainbased learning method is learning that involves maximizing the use of brain intelligence. In maximizing the intelligence of the brain, it is strongly influenced by the awareness of students and teachers of intelligence that stands out in every person. So the learning that will be implemented will determine the right learning strategy. Because the selection of learning strategies that are not right will have an impact on learning that can reduce the quality of intelligence of students in learning.